Prospective comparison of three predictive rules for assessing severity of community-acquired pneumonia in Hong Kong. Issue 4 (22nd November 2006) - Yan Man, Shin; Lee, Nelson; Ip, Margaret; Antonio, Gregory E; Chau, Shirley S L; Mak, Paulina; Graham, Colin A; Zhang, Mingdong; Lui, Grace; Chan, Paul K S; Ahuja, Anil T; Hui, David S; et al.
Abstract : Background: Community-acquired pneumonia (CAP) is a leading infectious cause of death throughout the world, including Hong Kong. Aim: To compare the ability of three validated prediction rules for CAP to predict mortality in Hong Kong: the 20 variable Pneumonia Severity Index (PSI), the 6-point CURB65 scale adopted by the British Thoracic Society and the simpler CRB65. Methods: A prospective observational study of 1016 consecutive inpatients with CAP (583 men, mean (SD) age 72 (17) years) was performed in a university hospital in the New Territories of Hong Kong in 2004. The patients were classified into three risk groups (low, intermediate and high) according to each rule. The ability of the three rules to predict 30 day mortality was compared. Results: The overall mortality and intensive care unit (ICU) admission rates were 8.6% and 4.0%, respectively. PSI, CURB65 and CRB65 performed similarly, and the areas under the receiver operating characteristic (ROC) curve were 0.736 (95% CI 0.687 to 0.736), 0.733 (95% CI 0.679 to 0.787) and 0.694 (95% CI 0.634 to 0.753), respectively. All three rules had high negative predictive values but relatively low positive predictive values at all cut-off points. Larger proportions of patients were identified as low risk by PSI (47.2%) and CURB65 (43.3%) than by CRB65 (12.6%). Conclusion: All three predictive rules have a similar performance in predicting the severity of CAP, but CURB65 is more suitable than the other two for use in the emergency department because of its simplicity of application and ability to identify low-risk patients.